The need for GPS data to be normalized for performance and fatigue monitoring in soccer: considerations for accelerations and decelerations - Pimenta, R.; Antunes, H.; Silva, H.; Ribeiro, J.; Nakamura, F. Y. (Strength and Conditioning Journal, 2026)
Load monitoring is an essential process for optimizing player performance, requiring accurate quantification of external training load. In soccer, locomotor-related external load is typically analyzed considering high-intensity actions such as sprints, high-speed running, and accelerations (ACC) and decelerations (DEC). Indeed, ACC and DEC represent a significant portion of the total external load produced by a soccer player during a game and vary considerably depending on factors such as playing position, competitive level, age category, and game-to-game variability. Furthermore, given the associated metabolic cost and increased eccentric component, these actions contribute to the development of high fatigue levels, as evidenced by increased biochemical and neuromuscular fatigue markers. However, several studies report ACC and DEC outputs using arbitrary absolute thresholds (AATs) to characterize ACC and DEC efforts, thereby neglecting the relative capacities of each soccer player. Consequently, quantifying ACC and DEC volumes using AATs may under- or overestimate individual soccer player performance by failing to consider their maximum ACC and DEC. Because inaccurate load monitoring may lead to underperformance and increased likelihood of injury occurrence, this review explores the plausible benefits of implementing normalization-based approaches to quantify ACC and DEC outputs, as opposed to relying on AATs.